Best Paper Award - Panayiotou, Tania; Chatzis, Sotirios P.; Ellinas, Georgios (My University, 2026)
Best Paper Award for the paper: Tania Panayiotou, Sotirios P. Chatzis, and Georgios Ellinas, “A Probabilistic Approach for Failure Localization,” Proc. 21st International Conference on Optical Network Design and Modeling (ONDM), 2017. https://www2.kios.ucy.ac.cy/best-paper-award-for-cyprus-based-research-team/
Keywords: Sciences